Pengelolaan Dana Bantuan Operasional Sekolah di SD N Kemasan I Surakarta - Subkhi Widyatmoko; S. Suyatmini (Universitas Muhammadiyah Surakarta, 2017)
This study aims to describe (1) Planning of school operational funds (BOS) (2)the implementation of school operational funds (BOS) (3) accountability of schooloperational funds (BOS) on Elementary School of Kemasan I Surakarta. This studyused a qualitative research with a ethnographic approach. The technique of collecting data through interviews, observation, and dokumentasi. Data analysis technique is done by using several stages of data collection, data reduction, data presentation, and data verification. Testing the validity of the data using triangulation techniques sources and methods. The results of the study concluded (1) in the planning process components involved, among others, the principal in charge, the school treasurer, board of teachers and school committee. The planning process begins with preparing RAKS (2) The implementation of BOS management begins with withdrawals made treasurer as required by leaving a minimum balance in the bank. Expenses that are not included in the 13 items in the governance of the BOS funds using dues infak students held every Friday. (3) The accountability of the BOS through a report done gradually every day. In the BOS management there are several books of governance must be made that the public treasury Books, General Treasury Ledger, Ledger and Ledger Bank Tax.